2018
DOI: 10.1002/pbc.27233
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing accrual to clinical trials of adolescents and young adults with cancer

Abstract: Underrepresentation of young people in cancer research is an international phenomenon and may contribute to poorer outcomes. We sought to identify systematically tested interventions and strategies to improve recruitment. The review identified 13 papers. The following four themes emerged: trial availability/regulatory factors; service configuration/place-of-care factors; recruitment methods and developmental factors specific to young people. We could not identify any studies that had employed prospective inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…This population is known to have lower involvement in clinical trials in comparison with children and older adults,22 58 yet there have been no targeted interventions developed to improve recruitment 59. We have reported that to optimise recruitment to clinical trials, what we have identified as ‘the 5 A’s’ need to be addressed, namely availability, accessibility, awareness, appropriateness and acceptability 58.…”
Section: Discussionmentioning
confidence: 99%
“…This population is known to have lower involvement in clinical trials in comparison with children and older adults,22 58 yet there have been no targeted interventions developed to improve recruitment 59. We have reported that to optimise recruitment to clinical trials, what we have identified as ‘the 5 A’s’ need to be addressed, namely availability, accessibility, awareness, appropriateness and acceptability 58.…”
Section: Discussionmentioning
confidence: 99%
“…While most AYAs believe participation will help themselves or others, fewer than 50% enroll in a trial during their cancer experience [4,7,8,9]. Barriers may be concrete, including sociodemographic factors and limited access to trials, as well as philosophical, including AYA trust in research processes, practical considerations for participation, and perceptions of trial acceptability [9,10,11,12,13]. These barriers are particularly important when it comes to psychosocial intervention research, where even fewer AYAs participate compared to pharmacology-based research [11].…”
Section: Introductionmentioning
confidence: 99%
“…Reasons reported to be common obstacles for accrual in clinical trials are often investigated independently a) nancial barriers (8), b) patient-reported factors (9, 10), c) physician-related factors (11), d) barriers encountered by selected patient population (12)(13)(14)(15)(16), or e) selected disease sites (17,18).…”
Section: Introductionmentioning
confidence: 99%